Thermal performance analysis and assessment of PCM backfilled precast high-strength concrete energy pile under heating and cooling modes of building. (5th November 2022) - Cao, Ziming; Zhang, Guozhu; Liu, Yiping; Zhao, Xu
Highlights: Numerical modeling of PHC energy pile considering phase change heat transfer is built. Effect of phase change material backfill (PCMB) on heat transfer of PHC energy pile is studied. Thermal response of soil around the PCMB-PHC energy pile is analyzed. PCMB thermal conductivity is most effective for enhancing the performance of PHC energy pile. Abstract: Thermal behavior of the precast high-strength concrete (PHC) energy pile with phase change material backfill (PCMB) has been rarely reported. In this study, a three-dimensional heat transfer model of a PHC energy pile with PCMB was developed to investigate the thermal response of PCMB-PHC energy pile under heating and cooling modes of building. Moreover, the effects of different PCMB properties on heat extraction and injection performances of PCMB-PHC energy pile were comprehensively evaluated using Taguchi-Grey relational analysis (Taguchi-GRA) method. The results indicate that increasing the PCMB thermal conductivity facilitates an enhancement in the heat transfer capacity of PCMB-PHC energy pile, and the total exchanged energy can be improved by 258.8 % (heating mode) and 256.8 % (cooling mode) as the PCMB thermal conductivity increases by 1 W/(m K). Increasing and decreasing the PCMB melting temperature of 4 ℃, the heat transfer capacity of PCMB-PHC energy pile rises by 19.3 % and 14.2 % under heating and cooling modes. In terms of PCMB latent heat, the heat transfer capacity of PCMB-PHC energy pile can be enhanced by 17.7 % (heating mode) and 12.6 % (cooling mode) with a 200 kJ/kg increase in PCMB latent heat. Furthermore, higher melting temperature (heating mode), lower melting temperature (cooling mode), and larger latent heat of PCMB can alleviate the fluctuation amplitude of soil temperature around the PCMB-PHC energy pile. Based on the Taguchi-GRA method, PCMB thermal conductivity (occupies 94.36 % and 93.75 % contribution percentages) is the most significant factor to affect the heat extraction and injection capacities of PCMB-PHC energy pile under heating and cooling modes, followed by PCMB melting temperature and latent heat. The results are useful for the performance optimization of PCMB-PHC energy pile in practical applications.